2015
DOI: 10.1002/jbm.b.33603
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of chitosan/gallic acid 3D microporous scaffold for tissue engineering applications

Abstract: This study explores the potential of gallic acid incorporated chitosan (CS/GA) 3D scaffolds for tissue engineering applications. Scaffolds were prepared by freezing and lyophilization technique and characterized. FTIR spectra confirmed the presence of GA in chitosan (CS) gel. DSC and TGA analysis revealed that the structure of chitosan was not altered due to the incorporation of GA, but thermal stability was significantly increased compared to the CS scaffold. SEM micrographs showed smooth, homogeneous, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…In vitro results have been more common to evaluate the biocompatibility of chitosan. For example, CS/GA scaffolds (0.5-1.0%) showed 60-75% viability at 24 h and 90% at 48 h. In addition, the images show an increased cell attachment for CS/GA scaffolds compared to CS scaffolds [43], demonstrating excellent cell viability and in vitro compatibility when chitosan-essential oil composites are used for tissue engineering applications.…”
Section: In Vivo Studiesmentioning
confidence: 92%
See 2 more Smart Citations
“…In vitro results have been more common to evaluate the biocompatibility of chitosan. For example, CS/GA scaffolds (0.5-1.0%) showed 60-75% viability at 24 h and 90% at 48 h. In addition, the images show an increased cell attachment for CS/GA scaffolds compared to CS scaffolds [43], demonstrating excellent cell viability and in vitro compatibility when chitosan-essential oil composites are used for tissue engineering applications.…”
Section: In Vivo Studiesmentioning
confidence: 92%
“…More studies are necessary to understand the mechanism of the resorption and degradation occurring. It has been demonstrated that a higher number of cells that adhered to the surface in CS-GA mixtures could be a result of the blending of GA with CS, which shields the highly positive charge density of CS, hence increasing cell attachment [43].…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4h) of the polymeric scaffolds is also a decisive property for the correct distribution and diffusion of oxygen and nutrients of the ingrowth tissues. 58,59 Summarizing, the developed GelMA/chitosan hydrogel with a dual crosslinking mechanism allows the printing of 3D structures with complex designs at high resolution.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…Tendency of tissue engineering researches to chitosan electrospinning scaffold is because of some underlying reasons. Firstly, chitosan is highly adaptable for a variety of applications(Thangavel, Ramachandran, & Muthuvijayan, 2016). Apart from this, lower deacetylate chitosan scaffolds possess smaller pore sizes, higher mechanical strength, moderate swelling properties and greater cellular activities(Dhandayuthapani, Krishnan, & Sethuraman, 2010;Sampath et al, 2016;Zhong et al, 2011).Raftery et al was developed a collagen hydroxyapatite scaffold loaded with chitosan nanoparticles carrying genes encoding osteogenic (BMP-2) and angiogenic (VEGF) proteins and applied for bone implantation at the site of critical size defect and results were showed that new bone formation significantly increased in animals that received composited scaffolds(Raftery et al, 2017).…”
mentioning
confidence: 99%